Universal whole-genome Oxford nanopore sequencing of SARS-CoV-2 using tiled amplicons - Ruslan Kalendar; Ulykbek Kairov; Daniyar Karabayev; Akbota Aitkulova; Nuray Tynyshtykbayeva; Asset Daniyarov; Zhenis Otarbay; Saule Rakhimova; Ainur Akilzhanova; Dos Sarbassov (Scientific Reports, 2023)
Abstract We developed a comprehensive multiplexed set of primers adapted for the Oxford Nanopore Rapid Barcoding library kit that allows universal SARS-CoV-2 genome sequencing. This primer set is designed to set up any variants of the primers pool for whole-genome sequencing of SARS-CoV-2 using single- or double-tiled amplicons from 1.2 to 4.8 kb with the Oxford Nanopore. This multiplexed set of primers is also applicable for tasks like targeted SARS-CoV-2 genome sequencing. We proposed here an optimized protocol to synthesize cDNA using Maxima H Minus Reverse Transcriptase with a set of SARS-CoV-2 specific primers, which has high yields of cDNA template for RNA and is capable of long-length cDNA synthesis from a wide range of RNA amounts and quality. The proposed protocol allows whole-genome sequencing of the SARS-CoV-2 virus with tiled amplicons up to 4.8 kb on low-titer virus samples and even where RNA degradation has occurred. This protocol reduces the time and cost from RNA to genome sequence compared to the Midnight multiplex PCR method for SARS-CoV-2 genome sequencing using the Oxford Nanopore.